LESSONS IN OLD MAN AND THE SEA - Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2013)
: In the novel The Old Man and the Sea the writer found some positive characters in the novel. During the analysis the writer applies structural genetic approach. The analysis shows that Santiago as character who performs spirit, motivation and hard worker. Then, Mandolin shows a helpful character. Then the setting of the Novel implies that a man should have a good relation with the nature.